Surface texture analysis of different focal knee resurfacing implants after 6 and 12 months in vivo in a goat model. Issue 10 (6th February 2022) - Aşık, Emin E.; Damen, Alicia H. A.; van Hugten, Pieter P. W.; Roth, Alex K.; Thies, Jens C.; Emans, Pieter J.; Ito, Keita; van Donkelaar, Corrinus C.; Pastrama, Maria
Abstract: The clinical success of osteochondral implants depends significantly on their surface properties. In vivo, an implant may roughen over time which can decrease its performance. The present study investigates whether changes in the surface texture of metal and two types of polycarbonate urethane (PCU) focal knee resurfacing implants (FKRIs) occurred after 6 and 12 months of in vivo articulation with native goat cartilage. PCU implants which differed in stem stiffness were compared to investigate whether the stem fixating the implant in the bone influences surface topography. Using optical profilometry, 19 surface texture parameters were evaluated, including spatial distribution and functional parameters obtained from the material ratio curve. For metal implants, wear during in vivo articulation occurred mainly via material removal, as shown by the significant decrease of the core‐valley transition from 91.5% in unused implants to 90% and 89.6% after 6 and 12 months, respectively. Conversely, for PCU implants, the wear mechanism consisted in either filling of the valleys or flattening of the surface by dulling of sharp peaks. This was illustrated in the change in roughness skewness from negative to positive values over 12 months of in vivo articulation. Implants with a softer stem experienced the most deformation, shown by the largest change in material ratio curve parameters. We therefore showed, using a detailed surface profilometry analysis, that the surface texture of metal and two different PCU FKRIs changes in a different way after articulation against cartilage, revealing distinct wear mechanisms of different implant materials.